Powder Surface Area and Porosity - Lowell, S. author. aut Link
XIV, 234 p.
Keywords: The rapid growth of interest in powders and their surface properties in many diverse industries prompted the writing of this book for those who have the need to make meaningful measurements without the benefit of years of experience. It is intended as an introduction to some of the elementary theory and experimental methods used to study the surface area, porosity and density of powders. It may be found useful by those with little or no training in solid surfaces who have the need to quickly learn the rudiments of surface area, density and pore-size measurements. Syosset, New York S. Lowell May, 1983 J. E. Shields Xl List of symbols Use of symbols for purposes other than those indicated in the following list are so defined in the text. Some symbols not shown in this list are defined in the text. d adsorbate cross-sectional area A area; condensation coefficient; collision frequency C BET constant c concentration D diameter; coefficient of thermal diffusion E adsorption potential f permeability aspect factor F flow rate; force; feed rate 9 gravitational constant G Gibbs free energy GS free surface energy h heat of immersion per unit area; height H enthalpy Hi heat of immersion Hsv heat of adsorption BET intercept; filament current k thermal conductivity; specific reaction rate K Harkins-Jura constant I length L heat of liquefaction M mass M molecular weight n number of moles N number of molecules; number of particles N Avagadro's number .